Online mindfulness meditation for mild cognitive impairment and mild dementia: A feasibility study protocol - Jiuhong You; Zunera Khan; Reena Swaroop; Yan Sun; Latha Velayudhan; Dag Aarsland (PLoS ONE, 2025)
Introduction Mild cognitive impairment (MCI) is an intermediate stage between normal aging and mild dementia. Patients with MCI and dementia usually experience impairment in cognitive functions such as memory, executive function, and processing speed. They may also develop neuropsychiatric symptoms, such as depression, anxiety, and agitation. While previous studies suggest that mindfulness meditation may benefit this population, the feasibility of delivering such interventions online remains unclear. Therefore, this study aims to investigate the feasibility and acceptability of an eight-week, online-delivered mindfulness program for people with MCI and mild dementia. Methods This study will recruit 32 participants over 60 years old with MCI or mild dementia in the UK. Participants will attend a weekly live online mindfulness meditation session, led by an experienced mindfulness teacher for eight weeks. Each session lasts 2.5 hours. In addition, participants will be encouraged to do daily home practice. The primary outcomes are feasibility and acceptability of an online program, assessed through participation records and semi-structured interviews. Secondary outcomes include participants' changes in cognitive function, mood, sleep, quality of life, mindfulness, and resilience. Discussion Mindfulness meditation delivered online could help reduce travel burdens and overall costs. This study aims to assess the usability and potential effects of online-delivered programs for this population, providing evidence to support the use of remote interventions in the care of older adults with cognitive impairments. Study registration ClinicalTrials.gov Identifier: NCT06768450.